PENINGKATAN PARIWISATA DI KABUPATEN GOWA MELALUI REVITALISASI GREEN PEKOE CAFÉ MALINO HIGHLAND - Alfina Rahel Tatundu; Uras Siahaan; Aarce Tehupeiory (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2025)
Malino is an area located in Tinggimoncong District which is a supporting area for South Sulawesi tourism which is located at an altitude of 1000 meters above sea level with natural beauty and cool air as a valuable asset to attract local and foreign tourists with the opening of tourist attractions including tea plantation tourist areas that have existed since the Dutch colonial era and then began to be managed with the addition of other facilities in 2014, namely Malino Highland. Malino Highland has experienced a decline in the number of tourists since 2020 which has had an impact until now. With its potential, Malino Highland is expected to be able to attract local and foreign tourists again, by conducting research using case study research methods for other tourist destinations in the Malino area supported by primary data obtained through observation, interviews, questionnaires, documentation and literature studies and the results show the need for revitalization to increase tourist attraction both in terms of area and buildings aimed at its main building, namely Green Peko'e Café by considering Sustainable Architectural Aspects and recommendations for transportation and access within the area. The use of sustainable materials is a consideration for use, namely Bamboo as the main material because it is widely found along Malino and can be harvested in just 3-5 years. By carrying out this Revitalization, it is hoped that Malino Highland can be an example of how to improve Tourism that pays attention to sustainable development in order to be an inspiration for tourism development in other areas.